TINJAUAN YURIDIS TERHADAP PUTUSAN DECLARATOIR YANG TIDAK DAPAT DIEKSEKUSI - Rezky Apdina Arzani (AkMen JURNAL ILMIAH, 2018)
The aims of this research are : (1) to understand and analyze the implementation of Article 74 paragraph (1) of Law to study verdict MARI number 739/PK/PDT/2011; (2) to understand and analyze legal steps can be taken to the request civil applicant if linked by Supreme court decision NO. 739 PK/PDT/2011 and No. 298/Pdt.G/2014/PN.Mks. The research method of this thesis is normative research. Supreme court decision no. 739/PK/PDT/2011. Based on the analysis that, incuding the contentiosa case, we may be found the declaratoir decision or condemnatoir decision. Decisions can be ececuted if they are in form of condemnatoir decision. If there is a decision that only list the declaratoir decision, and it was final and binding. So the legal action that can be filed is to file a new lawsit. The new lawsit demands to include condemnatoir decision, so the party can be forced to execute declaratoir decision. In the new lawsit, the plaintiff may also sue uitvoerbaar bij vooraad or decision necessarily because there has been a previous decision wich was final an binding.